METAFICTITONAL NARRATIVE QUALITIES OF CHIMERA - Farahbakhsh, Alireza; Yazdani, Narges Yeke (International Journal of Research -GRANTHAALAYAH, 2018)
This paper seeks to discern the narratological aspects of John Barth's famous essay titled “Literature of Exhaustion” in narrative qualities of his own novel, Chimera. Different narrative elements are discussed in the process of reading the essay; they include “The Construction and Deconstruction of Illusions in Chimera”, “The Orchestration of Polyphony of Voices”, “The Decadence of Mythology” and “Barth’s Success in the Pedagogy of Writing”. Each concept will be discussed in a separate section. The first section aims to discuss the concept of metafiction. Barth tries to represent the clash between real and represented worlds to confirm the fact that the boundary between reality and fiction becomes vague in the process of the novel. The second section focuses on "Heteroglossia" as one of the major themes of the novel. All of the characters represent Barth's voice in Chimera. The third section examines the influence of mythology and its decadence. The author attempts to advance a new method of writing by the traditional mimic forms and intertexual games. The last section intends to examine Barth's pedagogy of writing. He tries to create new fictions out of what already has been said in the world of fiction. The article concludes that Chimera is a rich postmodern novel that can be a role-model for writers to avoid originality and writer's block in writing.